Hip and groin injury management in English youth football: a survey of 64 professional academies. Issue 2 (3rd April 2018) - Light, Neil; Smith, Neal; Delahunt, Eamonn; Thorborg, Kristian
ABSTRACT: Objective : The purpose of this study was to determine the strategies used in English football academies to manage hip/groin injury. Methods : Eighty-six academies were invited to complete an online survey based on three themes related to hip/groin injury: (1) prevention, (2) screening and (3) return-to-play (RTP). Results : Sixty-four (74%) academies responded, of which fifty-two (81%) regularly conducted hip/groin injury prevention exercises, most commonly core/abdominal related, while only half of academies used high-load eccentric exercises. Fifty-three (83%) utilised screening measures for hip/groin injury, with adductor-strength testing commonly used in 40 (77%) academies, whilst patient-reported outcome measures were used infrequently (6%). Fifty (78%) academies followed a specific RTP protocol, often linked to player baseline scores, with adductor-strength deficits and pain on RTP tests commonly noted indicators of readiness to RTP. Conclusion : Most, but not all responding academies, address prevention, screening and RTP in their management of hip/groin injury. Many preventative exercises are utilised, with core/abdominal related exercises being the most common. Screening for baseline scores, in particular assessing adductor strength, is often used for gauging RTP post-injury. Most management methods described by academies link to current evidence-based literature; yet many elements of practice could be improved/standardised in the academy youth football level in the future.